An Optimal Path Identification in the Intermodal Freight Transportation Network - Gohari, Adel; Nasir Bin Matori, Abdul; Wan Yusof, Khamaruzaman; Toloue, Iraj; Cho Myint, Khin (International Journal of Engineering and Technology, 2018)
Intermodal transportation is a research topic of great interest at present. This paper presents a route choice analysis on an intermodal freight transportation network. The aim of this study was to determine the optimum route and mode of transportation based on least distance and least time criteria for the movement of containers from origin to the destination. Geographic Information System (GIS) was adopted to build the hypothetical freight transportation network and MATLAB software was used to model the travel distance and travel time. The results showed that the model can be used effectively to identify the shortest path and modes of transportation according to objective functions.Â Â